Designing For Super Diversity: Transcultural Identity, Participation and Place - Mesquita-Mendes, Nicole (MAJ - Malaysia Architectural Journal, 2025)
In the face of projected global displacement, there has been an increase in the phenomenon of super-diversity. Australia, facing increased immigration, is grappling with three pivotal challenges: the pragmatics of settlement, redefining identity, and managing cultural differences. This increase in super-diversity and its challenges requires us to reconsider how we design our cities and public spaces. This paper explores how transcultural identity instilled through participation and place identity can be embodied in Australian cities to support super-diversity while enhancing the existing sense of place. Through a literature review and cross-examination of three case studies: Superkilen (Denmark), Southport Community Centre (Australia) and Everyone, Everyday Initiative (England) – the research culminates in the synthesis of key participation and design strategies that support a transcultural participatory ecosystem. The paper results in the application of this framework to revitalise urban left-over spaces in Southport, Australia, to support the foundations of social cohesion: shared identity, access to opportunity and common purpose. The project’s significance lies in understanding how cities and public spaces can better address the challenges posed by super-diversity. The paper concludes that by integrating transcultural theory and Indigenous Australian philosophies with place identity and participation frameworks, Australian cities and public spaces can better support social cohesion in an era of super-diversity.